A systematic review and meta-analysis of beta-blockers and renin–angiotensin system inhibitors for preventing left ventricular dysfunction due to anthracyclines or trastuzumab in patients with breast cancer. (24th December 2021) - Lewinter, Christian; Nielsen, Torsten Holm; Edfors, Lars Robert; Linde, Cecilia; Bland, John Martin; LeWinter, M; Cleland, John G F; Køber, Lars; Braunschweig, Frieder; Mansson-Broberg, Agneta
Abstract: Aims: Trastuzumab and anthracyclines, often used in the treatment of breast cancer, may impair myocardial function, and reduce left ventricular ejection fraction (LVEF), potentially causing heart failure. Randomized controlled trials (RCTs) have evaluated the effects of beta-blockers (BBs), angiotensin receptor blockers (ARBs), and angiotensin-converting enzyme inhibitors (ACEI) on trastuzumab- and anthracycline-associated cardiotoxicity. We report a meta-analysis of these RCTs in patients with breast cancer. Methods and results: The primary analysis was on the effect of BBs and ACEI/ARBs on LVEF in patients treated with either trastuzumab or anthracyclines. A secondary analysis was done investigating the effect of BBs or ACEI/ARBs on LVEF in trastuzumab and anthracycline treatments. Only RCTs were included using the search term 'ARBs, ACEIs, BBs, anthracyclines, trastuzumab, and breast cancer' in PubMed, Embase, and CENTRAL up to 31 March 2021. A meta-analysis was conducted to estimate the mean difference (MD) in LVEF between intervention and placebo groups at follow-up. A total of nine RCTs ( n  = 1362) were included in the analysis. All patients were women. BBs and ACEI/ARBs were shown to attenuate the decline in LVEF during trastuzumab and anthracycline treatments [MD: 2.4; 95% confidence interval (CI): 0.3–4.2 and MD: 1.5; 95% CI: –0.6 to 3.7]. Compared with placebo, LVEF was significantly higher in patients assigned to BB or ACEI/ARB on trastuzumab (MD: 2.3; 95% CI: 0.0–4.6) but not on anthracyclines (MD: 1.9; 95% CI: –0.5 to 4.2). Conclusion: Both BB and ACEI/ARB therapies were associated with the preservation of LVEF during trastuzumab and anthracycline-containing regimens as compared with placebo, suggesting both to be beneficial. Structured Graphical Abstract: